2022
DOI: 10.3389/fonc.2022.921615
|View full text |Cite
|
Sign up to set email alerts
|

Primary Neuroendocrine Tumors of the Endometrium: Management and Outcomes

Abstract: ObjectiveTo analyze clinical behavior of, optimal treatment regimens for, outcomes, and prognosis of 170 patients with neuroendocrine tumors (NETs) of the endometrium.MethodsThe Surveillance, Epidemiology, and End Results database was used to identify patients with endometrial NETs diagnosed between 2004 and 2015. Clinical features and treatment regimens were analyzed, and 5-year overall survival (OS) and cancer-specific survival (CSS) were compared among different stages and treatment regimens. Univariate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…For advanced-stage tumors, platinum + etoposide chemotherapy is the recommended first-line treatment [77,108]. Of interest, an analysis of 170 patients with endometrial NETs from the SEER database, including SCNECs (N = 56), LCNECs (N = 60), and other NECs not elsewhere classified (N = 51), found that adding surgery to chemotherapy, with or without radiotherapy, may improve survival outcomes in patients with advanced disease [109], thus suggesting that surgery could be considered in select patients, when feasible. For locally advanced disease, radical surgery could be considered in selected cases (dashed line).…”
Section: Necs Of the Endometriummentioning
confidence: 99%
“…For advanced-stage tumors, platinum + etoposide chemotherapy is the recommended first-line treatment [77,108]. Of interest, an analysis of 170 patients with endometrial NETs from the SEER database, including SCNECs (N = 56), LCNECs (N = 60), and other NECs not elsewhere classified (N = 51), found that adding surgery to chemotherapy, with or without radiotherapy, may improve survival outcomes in patients with advanced disease [109], thus suggesting that surgery could be considered in select patients, when feasible. For locally advanced disease, radical surgery could be considered in selected cases (dashed line).…”
Section: Necs Of the Endometriummentioning
confidence: 99%
“…Endometrial neuroendocrine carcinoma (NEC) is a rare type of endometrial cancer that originates from endocrine cells in the neural ectoderm, neural crest, and neural endoderm [3] and is characterized by high invasive and metastatic potential. Endometrial NEC, also known as endometrial high-grade neuroendocrine neoplasm (NEN), accounts for less than 1% of all endometrial cancers [4]. NENs can occur in various organs and are frequently observed in the gastrointestinal tract (62-70%), followed by the lung (25%) [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…A previous retrospective study from the National Cancer Database (NCDB) showed that endometrial NEC patients had a worse prognosis than endometrioid endometrial carcinoma patients, and the hazard ratio (HR) of death was 2.32 (95% CI, 1.88-2.88) [8]. In addition, largecell neuroendocrine carcinoma has been found to have a greater risk of distant metastasis than small-cell neuroendocrine carcinoma [4]. However, due to its rarity, there are currently no guidelines or consensuses for the management of endometrial NEC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options include surgery, radiation therapy, and chemotherapy; however, the optimal management of this type of cancer is not well established[ 8 ]. The prognosis is generally poor with a high risk of recurrence and metastasis[ 2 ].…”
Section: Introductionmentioning
confidence: 99%